2008
DOI: 10.1111/j.1468-0297.2008.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Desperate Housewives? Communication Difficulties and the Dynamics of Marital (Un)Happiness

Abstract: This paper develops a model of marital dissolution based on communication difficulties. The quality of a marriage depends on the proximity of an action to a target. The target is unknown, and must be learned over time. Each individual receives private signals about the target, and can communicate them only imperfectly to his or her spouse. Because of imperfect communication, spouses may hold different beliefs about the optimal action. The action actually chosen is a compromise of the spouses' distinct beliefs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(91 reference statements)
0
7
0
1
Order By: Relevance
“…Communication difficulties play a vital role in marriage unhappiness and communications-related issues are cited much more often as causes for divorce than external issues, including economic ones ( Thompson, 2008 ). To better understand potential issues with communication, we analyzed the language that respondents used to answer open ended questions to our survey.…”
Section: Resultsmentioning
confidence: 99%
“…Communication difficulties play a vital role in marriage unhappiness and communications-related issues are cited much more often as causes for divorce than external issues, including economic ones ( Thompson, 2008 ). To better understand potential issues with communication, we analyzed the language that respondents used to answer open ended questions to our survey.…”
Section: Resultsmentioning
confidence: 99%
“…2 In order to continue with analytical rather than computational analysis, and especially to derive an expression for the hazard of new business formation as a function of time, I impose a form of myopia where the entrepreneur ignores the option value of remaining one more period with the current business. This approximation has been employed in similar problems by Jovanovic (1979), Thompson (2008b), and Thompson and Chen (2009). This implies the entrepreneur will form a new business at time t if 5which yields the approximate critical value…”
Section: The Model (1) Technologymentioning
confidence: 99%
“…In the same order of ideas, Thompson (2008) suggested that communication difficulties can put a marriage at risk, and quoted empirical evidence of this phenomenon.…”
Section: Happiness Gaps and Divorce In The Economic Literaturementioning
confidence: 99%